TI_GERICHTE 11.2021.4 vom 1. März 2021 , Irricevibilità di un appello contro un decreto di stralcio per desistenza - TI Tribunale d'appello (2021)
Irricevibilità di un appello contro un decreto di stralcio per desistenza